a) Để \(\left(d\right)\left|\right|Ox\) thì \(\Rightarrow\left\{{}\begin{matrix}m-1\ne0\\3m-4=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}m\ne1\\m=\dfrac{4}{3}\end{matrix}\right.\)
\(\Rightarrow m=\dfrac{4}{3}\)
b) Để \(\left(d\right)\left|\right|Oy\) thì \(\Rightarrow\left\{{}\begin{matrix}m-1=0\\3m-4\ne0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}m=1\\m\ne\dfrac{4}{3}\end{matrix}\right.\)
\(\Rightarrow m=1\)
c) Để \(O\in\left(d\right)\) thì \(\Rightarrow\left\{{}\begin{matrix}m-1\ne0\\3m-4\ne0\\-2m-5=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}m\ne1\\m\ne\dfrac{4}{3}\\m=-\dfrac{5}{2}\end{matrix}\right.\)
\(\Rightarrow m=-\dfrac{5}{2}\)
d) Để \(A_{\left(2;-1\right)}\in\left(d\right)\) thì \(\Rightarrow\left\{{}\begin{matrix}x=2\\y=-1\\\left(m-1\right)x+\left(3m-4\right)y=-2m-5\end{matrix}\right.\)
\(\Leftrightarrow2\left(m-1\right)-\left(3m-4\right)=-2m-5\\ \Leftrightarrow2m-2-3m+4=-2m-5\\ \Leftrightarrow-m+2=-2m-5\\ \Leftrightarrow m=-7\)